Detection of typhus antibodies by latex agglutination. - Hechemy, K E (1981)
A latex test for assay of antibodies to endemic and epidemic typhus rickettsiae is simple, group-specific, sensitive, and reproducible. Cross-reactivity within the typhus group was extensive.